Exploring the Impact of IoT and Blockchain on Supply Chain Management in Developing Countries - Rafifing, Neo; Mabina, Alton; Rafifing, Leatile W.; Mosinki, Joyce; Mphale, Ofaletse (Journal of Information System and Informatics, 2025)
The rapid development of the Fourth Industrial Revolution is having diverse effects on underdeveloped nations, influencing them in various ways. Developed countries have an advantage over underdeveloped countries since they embraced industrialization earlier, widening the gap between them. This comprehensive survey paper examines the multifaceted landscape of industry 4.0 in supply chain, shedding light on the potential challenges and key value drivers in the context of a developing country. Findings revealed that inadequate digital infrastructure, limited access to electricity, and a shortage of skilled workforce are the primary challenges faced by developing countries in the supply chain domain. The study systematically examines industry 4.0 technologies and indicates a 20-30% improvement in supply chain efficiency through the adoption of key technologies like IoT, AI, and blockchain. The study concludes by offering future research on industry 4.0 in supply chain management. The study results are assumed to offer insightful information to supply chain managers in developing countries, by enabling them with a deeper understanding of the major challenges and key drivers involved in integrating Industry 4.0 in their organizations and network.